Navigating multiple paradoxes - insights from family business leaders - Droste, Stefan (Cranfield University, 2024)
Managing conflicting objectives, for example, balancing short-term success with long-term survival, is challenging. Paradox literature suggests that conflicts regarding learning, performing, belonging, organising and control (Smith & Lewis, 2011) are persistent, containing coexisting, contradictory, and interdependent elements. Owners of family firms often pursue multiple goals, such as continuing a legacy, maintaining control and ensuring continued economic success. As a result, family firms are prone to paradoxes and provide an ideal context for paradox research. An examination of 3,370 articles revealed a research focus on isolated paradoxes, for example balancing management control and employee empowerment (Lewis et al., 2019), while only few studies explore a relationship between specific paradoxes (Jarzabkowski et al., 2013). However, while the work which acknowledges the interrelated nature of paradoxes argues that paradoxes influence each other, the paradoxes are still discussed as separate entities. This study investigates, therefore, if present paradoxes are influencing each other or if the paradoxes are interconnected intimately. This is done through a thematic analysis of interviews with 40 family business CEOs and owner-CEOs from a variety of industries. This research makes three key contributions. Firstly, it demonstrates the existence of a network of network of interconnected paradoxes, expanding paradox theory by showing that paradoxes are not isolated phenomena but instead form networks, which pose challenges to management. Secondly, the study introduces the Holistic Paradox Management (HPM) framework, which comprises four strategic focuses: Evolution, Alignment, Integration, and Stewardship. This framework provides a structured approach to navigating and understanding the networks of paradoxes within organisations. Thirdly, by focusing on the experiences of individual managers and employees, this study explains how personal values, identities, and cognitive biases influence both the formation of networks of paradoxes and their management.
Reinmoeller, Patrick - Associate Supervisor
Keywords: paradox; family business; networks of paradoxes; interconnected paradoxes; influencing paradoxes; thematic analysis